Application of an information system for inpatient nutrition management: An implementation study based on the Indonesian Minister of Health Regulation No. 26/2013 - Nora Lelyana; Aris Sarjito (AcTion: Aceh Nutrition Journal, 2025)
Nutritional management of hospitalized patients is critical for improving the quality of hospital services. The Indonesian Ministry of Health Regulation No. 26 of 2013 established standards for hospital nutrition management; however, its implementation has not been fully documented through digital systems. This study aimed to examine the application of information systems for inpatient nutrition management based on Regulation No. 26/2013. A descriptive qualitative approach was employed using content analysis of secondary data, including policy documents, nutrition unit reports, and outputs from hospital nutrition information systems in a Type B hospital from 2021 to 2023. The hospital was selected purposively based on the criterion of using a nutrition information system for a minimum of two years. The results showed that most components of the nutrition care strategy, such as initial assessment and diet provision, complied with regulatory standards, with over 80% of patients assessed within 24 h and 92,5% of diets appropriately provided. However, digital documentation of nutrition interventions and evaluations remained suboptimal (<40%), mainly because of manual recordkeeping, high workload, and limited training. In conclusion, although progress has been made in the implementation of nutrition management strategies, significant gaps remain in digital documentation. Strengthening information systems, improving human resource capacity through training, and routine monitoring are necessary to ensure compliance with the national standards.